Toxicity of botanical insecticides against the oil palm pollinating weevil, Elaeidobius kamerunicus faust - Johar, Muhammad Iqbal (2017)
Botanical insecticides are naturally occurring insecticides derived from any type of plants that can be formulated as insecticides. Botanicals insecticides are widely used due to their lower toxicity to human and environmental friendly. However, the use of these insecticides in the oil plam plantation can also affect the beneficial insects that act as pollinators. Elaeidobius kamerunicus is one of the essential beneficial insects for oil palm plantation in terms of pollinating activity. To ensure the botanicals insecticides product is harmless to the oil palm pollinating weevil, the toxicity of five types of botanicals insecticides namely, azadirachtin, garlic oil, 2 formulations of rotenone and cnidiadin were tested on the adult of E. kamerunicus. By using residual exposure method, adult E. kamerunicus were exposed individually to the insecticide residues for two hours then the insect were monitored daily for survivorship over a period of two days. The conditions of the insect after two days of exposure were recorded using three criteria that are alive, moribund or dead. By calculating the total insect moribund or dead, we estimated the efficacy of insecticides. Lethality index for the botanical insecticide was created in view of evaluation of immediate and delayed effect of insecticides exposure on the adult E. kamerunicus. At the end of experiment, azadirachtin showed the highest lethality index (58.89%) on the adult weevil, followed by plant based rotenone (57.22%), mineral based rotenone (50.00%), cnidiadin (41.67%) and garlic oil (6.67%). The high index values indicate the botanical insecticides tested give detrimental effect on the adult oil palm pollinating weevil, E. kamerunicus, except garlic oil.